PERANCANGAN GAME KONSENTRASI UNTUK PENYANDANG DISABILITAS BERBASIS ANDORID - Iqbal, Ahmad; Fauzi, Rahmat (LPPM Universitas Putera Batam, 2025)
The creation and design of an instructional Android game intended to enhance concentration in youngsters with impairments is covered in this study. The growing need for interactive learning aids that are accessible and inclusive was the driving force behind the initiative. The game was created using Unity and C#, with visual components created in Inkscape, following the Game Development Life Cycle (GDLC) testing. The black box testing was used for system testing, whereas observations, interviews, and questionnaires were used for data gathering. Children with a wide range of impairments may easily interact with the game thanks to its straightforward UI components, Large Buttons, and visually appealing environments. Beta testing with ten users, including parents and teachers, showed that the game was interesting, simple to use, and successful in assisting kids in concentration. Alpha testing verified that all features functioned as expected and without errors. Additionally, the game records user development so that parents and teachers can keep an eye on attention spans. According to the findings, this education game has great promise as a helpful resource for inclusive education, offering an enjoyable and engaging approach to enhancing cognitive attention.